2012
DOI: 10.1007/s00784-012-0681-9
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary rehabilitation of periodontally compromised patients with extensive one-piece fixed prostheses supported by natural teeth: a retrospective longitudinal study

Abstract: ObjectivesOral health-related quality of life is a relatively new but rapidly growing concept in dentistry. It is an aspect of dental health addressing the patient’s perception of whether his/her current oral health status has an impact upon his/her actual quality of life. Dentine hypersensitivity (DHS), which is a common condition of transient tooth pain associated with a variety of exogenous stimuli, may disturb the patient during eating, drinking, toothbrushing and sometimes even breathing. The resulting re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
0
9
0
1
Order By: Relevance
“…For indirect restorations, overhangs between 0.5 and 1 mm are associated with an increase in gingival inflammation and a more apical crestal bone level, while overhangs of less than 0.2 mm are not . Other studies showed that subgingival margins were associated with increased signs of gingival inflammation and, at times, increases in PD …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For indirect restorations, overhangs between 0.5 and 1 mm are associated with an increase in gingival inflammation and a more apical crestal bone level, while overhangs of less than 0.2 mm are not . Other studies showed that subgingival margins were associated with increased signs of gingival inflammation and, at times, increases in PD …”
Section: Resultsmentioning
confidence: 98%
“…A clear association is found between periodontal health and patient compliance with self‐performed plaque control and periodontal maintenance after prosthodontic therapy with fixed dental prostheses . In a prospective clinical trial where patients were instructed and motivated on adequate measures of self‐performed plaque control, plaque levels and gingival inflammation were not significantly different between teeth that received crowns and controls .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, two retrospective CS evaluated this comparison (Cordaro et al, 2005; Eliasson et al, 2007). The second PICO question (the efficacy of multi‐unit tooth‐supported fixed prostheses in patients with stage IV periodontitis) was studied in 18 investigations, including one RCT (Budtz‐Jorgensen & Isidor, 1987; Budtz‐Jørgensen & Isidor, 1990; Budtz‐Jorgensen et al, 1985; Isidor & Budtz‐Jorgensen, 1990), one CCT with split‐mouth design (Freilich et al, 1991), four prospective CS (Cortellini et al, 1999; Li et al, 2016; Nyman & Lindhe, 1979; Yi et al, 2001) and twelve retrospective CS (Baumer et al, 2011; Baumer et al, 2020; Brägger et al, 2011; Graetz et al, 2013; Guarnieri & Ippoliti, 2019; Heschl et al, 2013; Karlsson et al, 1995; Lundgren et al, 1975; Muller et al, 2013; Nyman et al, 1975; Quirynen et al, 1999; Yi et al, 1996; Yi, Ericsson, Carlsson, & Wennström, 1995). One investigation compared FPDs connecting teeth, implants, or teeth and implants with or without cantilevers (4 treatment arms for the purpose of this review) (Brägger et al, 2011), while another study included subjects receiving FPDs, removable partial dentures or no prosthetic treatment at all (for the purpose of the present review only data from the groups with FPDs and no prosthetic treatment were considered for the analysis) (Muller et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…O desconforto do paciente por ter que remover a prótese para higienização ou o aspecto estético dos grampos de retenção provavelmente são evidências de justificativa dos valores do OHIP-14 das PPRs estarem maiores, estatisticamente, que os das PPFs (Tabela 8). Özhayat e Gotfredsen (2013) divulgaram em sua pesquisa que as mulheres reabilitadas com PPRs foram o grupo que relatam os valores mais altos para o OHIP-14, mas que não há diferenças estatísticas entre os valores de OHIP-14 para os grupos PPR eCom relação aos fatores biológicos, podemos ressaltar que saúde bucal está intimamente relacionada com a presença ou não de placa bacteriana, que é o acúmulo de colônias bacterianas firmemente aderidas na superfície dos dentes ou outras superfícies sólidas bucais(Heschl et al 2013). No estudo de populações com…”
unclassified